Harmine derivative H-2-168 induces the death of Echinococcus granulosus by regulating mitochondrial fusion and fission - Yuehong Gong; Meiling Zhao; Meichi Pan; Yicong Zhao; Junpeng Liu; Hao Wen; Jianhua Wang (Pharmaceutical Biology)
Context H-2-168 has pharmacological effects similar to those of harmine, with less toxicity. The health of cells and organisms depends on a delicate balance between mitochondrial fusion and fission.Objective This study investigated the roles of H-2-168 and mitochondrial fusion and fission in Echinococcus granulosus.Materials and methods Notably, E. granulosus were isolated from fresh sheep livers, and then treated with H-2-168 (25 μg/mL), mitochondrial division inhibitor 1 (Mdivi-1, 25 μg/mL) or the combination of H-2-168:Mdivi-1 (25 μg/mL:12.5 μg/mL). After 24 h of culture, the indices related to E. granulosus were measured. Additionally, Drp1 was knocked down to explore its effects on E. granulosus growth.Results The EC50 values of H-2-168, Mdivi-1 and H-2-168:Mdivi-1 against E. granulosus were 44.171, 117.882 and 32.924 μg/mL, respectively. Compared with H-2-168 or Mdivi-1, the combination of H-2-168 and Mdivi-1 showed better inhibitory effects on E. granulosus viability, as well as increased levels of ROS and LDH, decreased ATP levels, inhibited mitochondrial activity and reduced mitochondrial membrane potential (p < 0.05), with the upregulation of Caspase-3, Cyt-c, Drp1, Fis1 and downregulation of Bcl-2, Mfn2 and OPA1. Additionally, Drp1 knockdown was successfully performed in E. granulosus, which significantly inhibited E. granulosus viability (p < 0.05) and further downregulated Mfn2 expression induced by H-2-168.Discussion and conclusion Drp1 is closely associated with mitochondrial fusion and fission, and H-2-168 may promote E. granulosus death through disrupting the balance between mitochondrial fusion and fission.